Effect of Heating, Ventilation, and Air Conditioning (HVAC) system on indoor air quality in a medical facility / Fauzi Baharudin ... [et al.] - Baharudin, Fauzi; Mohd Adlan, Nur Fatt-Hiyyah; Kassim, Jalina; Hamzah, Nurhidayah; Ghazali, Suriati (2023)
Indoor Air Quality (IAQ) refers to the stationary air within an inhabited or occupied structure. Previously, there were fewer studies on indoor air quality in medical facilities in Malaysia especially in Terengganu. Most indoor air quality issues are caused by insufficient Heating, Ventilation, and Air Conditioning (HVAC) systems, which regulate three parameters. The purpose of this study is to assess the indoor air quality of a medical facility and determine if it complies with the Industry Code of Practice 2010 (ICOP 2010) and ASHRAE 170-2017. In this investigation, a total of 3 locations namely Administration Office, Surgical Outpatient Department (SOPD) waiting area and Ophthalmology Consultation Room in Hospital Sultanah Nur Zahirah (HSNZ) were evaluated. Walkthrough inspections were done at the locations before data collection to determine the IAQ. Two IAQ meters, notably VelociCalc and Testo, were used to collect data to assess the temperature, relative humidity, and air flow of the selected locations. Samples were taken every 2 hours for each location from 8 a.m. to 5 p.m. The data then were analysed. All three locations' temperatures were lower than ICOP 2010's acceptable limit (23-26°C), but still within ASHRAE 170-207's 21-24°C range, except for the SOPD waiting room. All three locations met ICOP 2010 and ASHRAE 170-207 relative humidity standards. Meanwhile, only the SOPD waiting room had an appropriate air flow of 0.16-0.17m/s per ICOP 2010. The study also revealed that there was a correlation between the number of occupancies and the performance of HVAC system with the indoor air quality level.